GLYCEROL REMOVAL FROM BIODIESEL USING SOLVENT- AIDED CRYSTALLIZATION TECHNIQUE - Letchumanan, Arun (IRC, 2019)
“Production and consumption of biodiesel have increased nowadays as an alternate fuel compared to fossil fuels. This is because, biodiesel is a renewable, biodegradable fuel that can be produced from the natural resources such as vegetable oils and animal fats and has positive effects towards the environment. Vegetable oil undergoes transesterification chemical reaction with an alcohol in the presence of catalyst which results in formation of fatty acid methyl ester (FAME) phase and glycerol layer that must be removed. The common purification of biodiesel using water washing step generates high amount of wastewater with high content of organic compounds that can harm the environment. This report discusses the removal of glycerol from biodiesel using solvent-aided crystallization as waterless purification method. In order to comply with the international standards of biodiesel, the FAME phase was tested for total glycerol compositions after being removed via solvent-aided crystallization technique.